Vectors and Spatial Patterns of Angiostrongylus cantonensis in Selected Rice-Farming Villages of Muñoz, Nueva Ecija, Philippines - Ma. Angelica A. Tujan; Ian Kendrich C. Fontanilla; Vachel Gay V. Paller (Journal of Parasitology Research)
In the Philippines, rats and snails abound in agricultural areas as pests and source of food for some of the local people which poses risks of parasite transmission to humans such as Angiostrongylus cantonensis. This study was conducted to determine the extent of A. cantonensis infection among rats and snails collected from rice-farming villages of Muñoz, Nueva Ecija. A total of 209 rats, 781 freshwater snails, and 120 terrestrial snails were collected for the study. Heart and lungs of rats and snail tissues were examined and subjected to artificial digestion for parasite collection. Adult worms from rats were identified using SSU rDNA gene. Seven nematode sequences obtained matched A. cantonensis. Results revealed that 31% of the rats examined were positive with A. cantonensis. Rattus norvegicus and R. tanezumi showed prevalence of 46% and 29%, respectively. Furthermore, only Pomacea canaliculata (2%) and Melanoides maculata (1%) were found to be positive for A. cantonensis among the snails collected. Analysis of host distribution showed overlapping habitats of rats and snails as well as residential and agricultural areas indicating risks to public health. This study presents a possible route of human infection for A. cantonensis through handling and consumption of P. canaliculata and M. maculata or crops contaminated by these snails.